Potret Tubuh Perempuan dalam Iklan Body Lotion: Analisis Wacana Kritis Norman Fairclough - Suhartatik Suhartatik; Moh. Hafid Effendy; Agus Purnomo Ahmad Putikadyanto; Sultan Sultan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This research was motivated by the researcher's interest in uncovering the meaning behind body lotion advertisements, which the majority of women used as objects of advertising study. The aim is to describe the portrait of women's bodies in Body Lotion advertisements using Norman Fairclough's critical discourse analysis theory. The appearance of women in various mass media, such as print, visual and electronic media, does not fully represent an appropriate space for viewing women critically regarding their position in society, socio-economics, even in the realm of political solidarity. This research uses a qualitative descriptive method to examine the language used in Body Lotion advertisements. especially those depicting portraits of women's bodies. The results of this research indicate that critical discourse analysis of women in Body Lotion advertisements places more emphasis on social analysis and institutional context of language and discourse. This can help us understand the language of Body Lotion advertising to women produced and disseminated in the context of marketing policies and the cosmetics industry which is dominated by large companies.